A Socioenactive Perspective on Emotion Contagion and Senses: Analyzing the Phenomenon via EEG Signals - Espinoza Taype, Geovanna Evelyn; Dos Reis, Julio Cesar; Calani Baranauskas, Maria Cecília (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
Emotion contagion is a phenomenon in which emotions are transmitted from one to another in social interactions. In this process, our senses are involved because our body perceives the environment through them. Many activities are triggered between our mind, body, and the space around us involving sensory-motor, perception, and cognition aspects. All the aforementioned aspects are studied by the Socioenactive perspective in the frame of relationships connecting the social, physical, and digital worlds. This research explores the Socioenactive perspective into the emotion contagion phenomenon in the interaction with computational systems. Our study used an EEG device to collect brain wave data from 21 participants in a scenario of potential emotional contagion. Our analysis adopted the Transform Fourier technique to get features in brain wavelets of happiness, fear, anger, and sadness emotional states. The brain waves analysis considering the amplitude and frequency allows for finding features associated with each kind of emotional state. A post-experiment questionnaire was used to gather self-reported emotional states from participants. We investigated the relations between emotional states data gathered by the self-report and by brain waves directly. The results shown through the self-report and brain waves indicate that 71% of participants felt the happiness emotion; 38% of participants felt the sadness emotion; the fear and anger emotion resulted in 24% and 19% of the cases, respectively.